(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The study adresses the problem of maintaining the operability of settling tanks designed for storing contaminated liquids. The study provided a method of mixing of bottom sludge and a mathematical model for determining initial velocity of outflow from the flat orifice depending on physical, mechanical and rheological parameters of the bottom sludge.